THE IMPACT OF CHANGING THE APPEARANCE OF A PERSON ON THE PROPERTY OF THE NEUROPSYCHIC SYSTEM THROUGH AESTHETIC SURGERY - Polvanov, R.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
the appearance of a person often affects his essence, his inner world and his behavior. Based on the analysis, a rational conclusion can be made by comparing the appearance of the nervous system with the postoperative state after surgical replacement of the appearance of our patients under observation. Materials and methods: Examination, history taking, analysis of the patient's preoperative and postoperative plastic surgery, laboratory and instrumental leaflets and a visual-objective examination based on the history of the disease. Results: 28 (89.3%) of 28 patients with successful plastic surgery had positive mental and behavioral changes. Because of their appearance, which was more attractive and flawless than the preoperative period, it was disfigured, dissatisfied with the environment, was at a disadvantage due to anxiety and depression. Conclusions: In our observations, it was noted that approximately 30% of patients aged from 30 to 45 years old accounted for about half (42.4%) of the total number of applicants, of whom 33 had 22 (66.7%) city residents and 11 were rural (33.3%) as well as their attractiveness and attractiveness, and the urban population pays more attention to these aspects than the rural population.